Association of delayed chronotype with allergic diseases in primary school children. (3rd June 2022) - Chen, Yiting; Zhao, Anda; Lyu, Jiajun; Hu, Yabin; Yin, Yong; Qu, Jiajie; Tong, Shilu; Li, Shenghui
ABSTRACT: To investigate the associations of sleep midpoint for both weekdays and weekends, and chronotype, with allergic diseases, specifically asthma, allergic rhinitis, and eczema in primary school children. In this cross-sectional study, we evaluated 10409 children between 7 and 12 years of age (mean 9.21 ± 1.51 years; male 52.2%). Each allergic disease was defined as children with both diagnosed disease and current symptoms, and the reference group was described as children without any allergic symptoms. Sleep durations and mid-sleep times were calculated by reported sleep timing. Chronotype was determined by mid-sleep time on free days corrected for oversleeping. Children with allergies have shorter sleep duration and later sleep preferences. Late weekly sleep midpoints were associated with higher odds of allergies, and the odds were even higher for later weekday midpoints than their weekend counterparts. Regarding chronotype, the more evening chronotype, the higher the odds of allergic rhinitis and eczema. Additionally, effect of weekday late sleep midpoint on allergies was stronger as the participants who slept less (asthma: aOR, 1.62, 95 CI%, 1.25–2.10, p < .001; allergic rhinitis: aOR, 2.12, 95 CI%, 1.68–2.67, p < .001; eczema: aOR, 1.94, 95 CI%, 1.52–2.48, p < .001). Further, the associations of chronotype with allergic rhinitis were confounded by second-hand smoking exposure. Our study, which finds an association between chronotype and the odds of three allergic diseases, hopes to improve sleep health awareness, especially in the particular population with allergic diseases, and describes the importance of evaluating modifiable behavioral factors, such as sleep habits, as a plausible factor for the prevention and treatment of allergic diseases.